Jabal Amil: la génesis del activismo chií contemporáneo - Rabih Menem, Issam; Regina Ferabolli, Silvia (El Colegio de México A.C., 2024)
This article aims to demonstrate that the secular activism of traditional Shiite families from Jabal Amil in southern Lebanon lies at the origin of transformative social and political phenomena in the contemporary Shiite world, particularly the Sadrist, Amal, and Hezbollah movements. The primary objective is to investigate the complex network that shapes the relationships between members of the Shiite community of Jabal Amil and their co-religionists in other parts of the Middle East, especially in Iran, Iraq, and Lebanon, and to analyze how the connections of these influential Shiite families transcend national borders. To achieve this aim, the article draws on Constructivist theory and employs the method of Social Network Analysis (SNA). It concludes that belonging to a historic transnational network rooted in Jabal Amil mobilizes, legitimizes, and empowers the main Shiite leadership of the contemporary era.